EFEKTIVITAS PENERAPAN PEMBELAJARAN IPA FISIKA BERBASIS MULTIREPRESENTASI TERHADAP PEMAHAMAN KONSEP PADA MATERI CAHAYA KELAS VIIII DI SMPN 12 PEKANBARU - Parindra Firmando; Fakhruddin '; Syahril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this reaserch is to find out The effectiveness ofmultirepresentation-based physics science learning application toward theunderstanding of light material concept at the VIII grade of SMPN 12 Pekanbaru. Thesample of this research is 39 students of the VIII grade. The research design is preexperimentalin the form of one shot case study. This research uses a test as theinstrument. There are 7 questions in the test based on the indicator of Bloom theoryconcept understanding. The data will be analyzed by using descriptive analysistechnique by looking at the learning result of students’ physics concept understandingby using the criteria of absorption and learning effectiveness. For the result, theresearcher gets the mean score of the students’ absorption is 81,68% which means thestudents are in good category. Based on all the indicators of concept understanding, itis found that the indicator of classifying is the highest indicator 98,72% (very good)while the indicator of comparing is the lowest 64,74% (good enough). Then, it can beconcluded that the application of multirepresentation-based physics science learning iseffective to be applied in light material at the VIII grade of SMPN 12 Pekanbaru.Keywords: Effectiveness, Understanding Of Concept, Multirepresentation